Teaching Latin and Greek in primary classrooms: the Classics in Communities project - Holmes-Henderson, A (Cambridge University Press, 2016)
The Classics in Communities project (http://classicsincommunities.org/) is a partnership between members of the University of Oxford, the University of Cambridge and the Iris Project. It was set up in response to the primary curriculum reforms which were implemented in England from September 2014. In the Key Stage 2 (KS2) Languages curriculum policy, for the first time, Classical Greek and Latin can be chosen for study by pupils aged 6-11 in place of a modern language. The project particularly targets schools where Classical languages have not previously featured on the curriculum. It has twin aims: to equip teachers in primary schools with the skills and knowledge necessary to teach these languages; and to conduct parallel research to determine the impact of Classical language learning on children's cognitive development.